Evaluation of micronuclei in potentially malignant disorders and oral cancers: A cytological assay - Aishwarya Bhatnagar; Madhav Nagpal; Jyothi S Kumar; Anamika Joshi; Sudhir Baroopal; Kailash Kewalia (Wolters Kluwer Medknow Publications, 2023)
Objective: The present study aims to evaluate the number of micronuclei (MN) in potentially malignant disorders (PMDs) and oral cancer and correlates them with the control group. Materials and Methods: Subjects included in the study were equally divided into four groups. Exfoliated cells were then obtained from the buccal mucosa using cytological brush. Smears were stained using rapid Pap stain. The smears were observed using a light microscope, and MN was counted out of 10 high-power fields and scored according to PE Tolbert (1992) criteria. Results: The mean MN count was found to be 0.23, 2.10, 3.03, and 3.57 in groups I, II, III, and IV, respectively. The overall intergroup comparison between the four groups was found to be statistically significant with a P value less than 0.05. Conclusion: This study gives a fair assessment that MN assay in exfoliated cells of oral epithelium can be a conducive biomarker while screening for PMDs of the oral cavity in doubtful lesions that are primarily misdiagnosed clinically.